Found in Translation or Edwige Danticat’s Voyage of Recovery - Malena, Anne (TTR, 2003)
AbstractThis paper explores the writing of Haitian writer Edwige Danticat from a perspective of (im)migration and translation which is different from that elaborated by Eva Hoffman in Lost in Translation. By contrasting the traumas suffered by both authors and the way they deal with it, different conclusions can be reached concerning the theory of self they propose. Hoffman is resigned to translate herself in order to fit into the American context but never gets over the loss of her Polish self. Danticat, who realizes upon her arrival in New York that she was already a translated being, delves into the Haitian collective past for the creation of fictional characters who find in the translation of their selves the strength to live in two languages and two cultures without abandoning their personal and collective past.